2006
DOI: 10.1155/jbb/2006/19365
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Neuronal Death in Synucleinopathy

Abstract: α-synuclein is a key molecule in the pathogenesis of synucleinopathy including Parkinson's disease and multiple system atrophy. In this mini-review, we mainly focus on recent data obtained from cellular models of synucleinopathy and discuss the possible mechanisms of neurodegeneration. Recent progress suggests that the aggregate formation of α-synuclein is cytoprotective and that its precursor oligomer (protofibril) may be cytotoxic. The catechol-derived quinones are the candidate molecules that facilitate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
(42 reference statements)
0
18
0
Order By: Relevance
“…Thus, these data suggested that the serine 129 phosphorylation was required not only for aggregate formation but also for the induction of ␣-synuclein toxicity. Because the toxic effect of ␣-synuclein was suggested to be associated with intermediate oligomer formation, so-called protofibrils (23,45), the phosphorylation of ␣-synuclein at serine 129 may be important for the formation of protofibrils. A recent study using NMR also suggested that serine 129 phosphorylation may destabilize the intramolecular interactions, converting ␣-synuclein into more unfolded forms that self-associated readily (46).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these data suggested that the serine 129 phosphorylation was required not only for aggregate formation but also for the induction of ␣-synuclein toxicity. Because the toxic effect of ␣-synuclein was suggested to be associated with intermediate oligomer formation, so-called protofibrils (23,45), the phosphorylation of ␣-synuclein at serine 129 may be important for the formation of protofibrils. A recent study using NMR also suggested that serine 129 phosphorylation may destabilize the intramolecular interactions, converting ␣-synuclein into more unfolded forms that self-associated readily (46).…”
Section: Discussionmentioning
confidence: 99%
“…including oxidative stress (Hasegawa et al 2003(Hasegawa et al , 2007Hasegawa 2010), endoplasmic reticulum stress (Sugeno et al 2008;Mercado et al 2016), mitochondrial dysfunction (Mizuno et al 1998;Rothfuss et al 2009), misfolded protein toxicity Takeda et al 2006), ubiquitin-proteasome dysfunction Vilchez et al 2014;Matsuda 2016), neuroinflammation , impairment of the autophagy-lysosome system (Ferrucci et al 2008;Oshima et al 2016), and alterations in the membrane trafficking pathway (Abeliovich and Gitler 2016). Among them, recent advances in clinical genetics and studies using model organisms have emphasized that the membrane trafficking pathway contributes immensely to the pathogenesis of PD and related neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this effect was increased by the familial PD-linked mutants A30P and A53T [216] but not by the mutant E46K [217]. Thus, although pore formation may be involved insynuclein-induced toxicity, other mechanisms also have been implicated, but these are not well understood [218].…”
Section: Oligomers Of Disease-related Amyloido-genic Proteins Other Tmentioning
confidence: 99%